Income Stability and Sustainability in the Colombian Coffee Supply Chain from the Farmers’ Perspective - Komár, Daniel (2025)
In this thesis, the author examines how smallholder coffee farmers in Colombia can achieve improved income stability and long-term economic sustainability. Four specific aims guided the analysis: I. Analyze income distribution across the Colombian coffee supply chain; II. Identify conditions that reduce dependency on volatile market-based pricing; III. Assess whether these conditions also enable farmers to reach sustainable income benchmarks; IV. And provide practical recommendations based on the findings. The study combines descriptive statistical analysis with crisp-set Qualitative Comparative Analysis (QCA). The empirical part draws on a dataset of 143 coffee lots from the Huila region provided by the Czech importer Chicas Industry. Additional reference data were obtained from the Colombian National Coffee Federation (FNCC), the international C-market, and benchmark thresholds from the Sustainable Coffee Buyer’s Guide (SCBG). The analysis focuses on identifying combinations of structural and commercial conditions that support higher farm gate prices and help farmers reach income levels defined as sustainable. The first aim was fulfilled through a quarterly-based value distribution analysis, which showed that farmers captured, on average, around 60% of the final price. Importers’ margins, however, were found to be substantial and highly variable, indicating their influence on the final price formation. While both farm gate and FNCC prices generally aligned with global market trends, pricing in relationship-based trade displayed a degree of independence from the C-market, suggesting the potential for reduced dependence on global volatility. To address the second aim, QCA was applied to identify conditions consistently associated with above-median farm gate prices. The results highlighted high coffee quality as the most reliable individual predictor of better price outcomes.